0688 Is Sleep Continuity Disturbance and Problem Endorsement Uniformly Worse with Age?. (12th April 2019) - Boyle, Julia T; Williams, Natasha; Grandner, Michael; Vargas, Ivan; D'Antonio, Breanna; Seewald, Mark; Muench, Alexandria; Ellis, Jason; Posner, Donn; Rosenfield, Bradley; DiTomasso, Robert A; Perlis, Michael L
Abstract: Introduction: Older adults are thought to be particularly prone to insomnia. What is less clear is the extent to which this general observation 1) applies to specific measures and 2) corresponds to sleep dissatisfaction. The aim of the present analysis was to evaluate how sleep continuity disturbance (SCD) and problem endorsement vary by age. Methods: An archival analysis was conducted with an existing database of 4, 206 individuals who completed an online screening survey (www.sleeplessinphilly.com ) . Subjects were grouped into four age categories (matched for race, BMI, and gender): Young Adults (YA[18-29]), Adults (A[30-44]), Middle Aged Adults (MA[45-65]) and Older Adults (OA[65-89]). One-way ANOVA's were utilized to evaluate differences between groups for sleep latency (SL), number of awakenings (NWAK), wake after sleep onset (WASO), early morning awakenings (EMA), and total sleep time (TST). Problem endorsements (i.e., "do you consider this a problem?") were assessed with Contingency and/or Chi-Square analyses for each SCD variable. Results: Each group was comprised of 180 subjects (total n=720, 55% female). Sleep initiation problems did not become more severe with age. In contrast, sleep maintenance problems worsened with age (> WASO, > EMA, < TST). Problem endorsements appeared to parallel severity trends. Mean severity data are as follows. SL ([All: 42.2min]; [YA:43.2]=[A:45.6]=[MA:39.9]=[OA:40.0], p = 0.213); NWAK ([All: 2.6]; [YA:2.2]<[A:2.8]=[MA:2.8]=[OA:2.7], p = 0.001); WASO ([All: 37.6min]; [YA:22.6]<[A:36.1]=[MA:40.9]=[OA:45.7], p < 0.001); EMA ([All: 61.8min]; [YA:53.1]=[A:57.5]=[MA:63.8]=[OA:71.2], p < 0.001); and TST ([All: 342.1min]; [YA:365.7]>[A:334.7]=[MA:326.3]=[OA:341.7], p < 0.001). Percent problem endorsement data are as follows. SL ([All: 76.4%]; [YA:69.9%]<[A:82.8%]=[MA:75.0%]=[OA:78.0%], p = 0.045); NWAK ([All: 77.3%]; [YA:62.2%]<[A:83.8%]=[MA:80.9%]=[OA:81.4%], p < 0.001); WASO ([All: 85.5%]; [YA:69.7%]<[A:87.4%]=[MA:91.6%]=[OA:89.6%], p < 0.001); EMA ([All: 76.6%]; [YA:58.4%]<[A:82.8%]=[MA:78.4%]<[OA:84.9%], p < 0.001); and TST ([All: 72.4%]; [YA:56.1%]<[A:76.1%]=[MA:78.9%]=[OA:78.3%], p < 0.001). Conclusion: More sophisticated analyses are on-going to determine the degree to which SCD symptom severity predicts the likelihood of problem endorsement, and what other factors may influence the report of sleep satisfaction, and whether these vary with age. Support (If Any): Perlis NIH:R01AG041783;K24AG055602;R01AT003332